PENGEMBANGAN SCRAPBOOK ETNOMATEMATIKA PADA MATERI JARING-JARING BANGUN RUANG UNTUK SISWA SEKOLAH DASAR - Devi Laili Maesaroh; Muh Muhaimin (JURNAL MathEdu (Mathematic Education Journal), 2026)
Mathematics learning in elementary schools still faces challenges, particularly in the topic of solid figure nets, which is abstract and requires contextual and engaging learning media. This study aimed to develop an ethnomathematics-based scrapbook learning media and determine its validity and practicality for teaching solid figure nets. This research employed the Research and Development (R&D) method using the ADDIE model, consisting of the Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects included two expert validators, one fifth-grade teacher, and 30 fifth-grade students of SD Negeri 3 Mantingan. Data were collected through observation, interviews, documentation, validation questionnaires, and response questionnaires. The results showed that the material expert validation reached 96% and the media expert validation reached 100%, both categorized as Highly Valid. The practicality test obtained 98% based on the teacher's responses and 98% based on the students' responses, both categorized as Highly Practical. Therefore, the ethnomathematics-based scrapbook learning media is considered highly valid and practical for teaching solid figure nets in elementary schools.